Wpływ stosowania idei społecznej odpowiedzialności na wyniki finansowe – ocena istotności statystycznej na przykładzie przedsiębiorstw działających w Polsce - Beata Mirowska (Studia i Materiały)
Currently, the ideas of social responsibility are widely used in business management, and became important criteria of their assessment, at the same time there is a cognitive gap in area of the impact of CSR on the financial results of companies. The purpose of this article is to try to answer the following questions: is the pursuit of companies’ policies focused on corporate social responsibility CSR (Corporate Social Responsibility) influences the financial results CFP (Corporate Financial Performance)? Attempting realization of taken assumption, the following hypothesis is taken, there is a statistically significant relationship between the use of CSR and financial results of enterprises. In the article special attention is given to the impact of CSR on the net result, return on assets and return on sales, because those are the basic indicators identifying the company’s financial condition. The results of the study indicate opublikowathat statistically CSR does not have a significant impact on the value of the financial result, as well as on return on assets and return on sales.